Impact de l’apprentissage systémique sur la motivation à apprendre des étudiants dans un contexte d’apprentissage en milieu clinique - Sonia Soussi; Abdelmajid Naceur; Dominique Berger; Atf Ghérissi; Amina Belgacem; Ihsen Zairi (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The environment, pedagogical approaches and methods are determining factors for students’ motivation to learn. In higher education in health sciences, the pursuit of motivational dynamics remains a subject that has been poorly documented, especially in the context of clinical learning. In response to this lack, a mixed-method study was conducted with third-year students enrolled at the Higher School of Health Sciences and Techniques in Tunis in order to compare the effects of learning by objective and systemic learning on their motivation. The data collection concerned 172 students in pre-test and 165 students in post-test, carried out using the “Motived Strategies Learning Questionnaire” in its translated and validated version according to the Vallerand method (1989). Twelve students were the subject of a group interview. The overall average on the six motivation scales showed a marked improvement in favour of the systemic learning model with the exception of the test anxiety scale. The overall average score was 3.93 (S-D = 0.81) for the objective approach and 4.94 (S-D = 0:53) for systemic learning. These results revealed a significant statistical difference, showing an appreciable advantage in favour of systemic learning. The students’ comments confirmed the statistical results giving a lot more arguments.